PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI SD NEGERI SENDANGHARJO NGASEM KABUPATEN BOJONEGORO - Susanti, Putri; Nafi’ah, Binti Azizatun (Jurnal Pendidikan Dasar, 2022)
Education has a function to develop capabilities and improve the quality of human resources of a nation and state. Government policy in an effort to improve education in Indonesia is the School Operational Assistance (BOS) policy. Management of the BOS itself is the responsibility of the headmaster, school treasurer, and also the school committee. The purpose of this study was to analyze the management of the School Operational Assistence fund (BOS) in SD Negeri Sendangharjo Ngasem Bojonegoro Regency from the planning, implementation, and reporting stages. The research method used by the author is a type of descriptive approach with a qualitative approach, namely the data obtained by the author is from data collection and other litelature. Describes the condition og SD Negeri Sendangharjo Ngasem Bojonegoro Regency in managing the School Uperational Assistance Fund (BOS). The type of data used is primary and secondary data. Primary data is data obtained from interviews with school treasurers. Secondary data is data that has been collected before, either, through books, articles, journals, and others. The results showed that the management of BOS funds an SD Negeri Sendangharjo Ngasem Bojonegoro Regency, was in accordance with the directions from the Bojonegoro Regency Education Office.